Common framework on financing agricultural and rural extension - Technical Centre for Agricultural and Rural Cooperation; Neuchâtel Group (CTA / Neuchâtel Group, 2007)
Following the formulation of the Common Framework for agricultural extension in sub-Saharan Africa (see 1408), the Neuchâtel Initiative Group supported more in-depth field studies and published this elaboration of the earlier framework, which takes into account new mechanisms aimed at mobilising resources to support rural services.